The Stoichiometry of Carbon, Hydrogen, and Oxygen in Peat. Issue 10 (2nd October 2018) - Moore, Tim R.; Large, David; Talbot, Julie; Wang, Meng; Riley, John L.
Abstract: Carbon (C), hydrogen (H), and oxygen (O) form ~90% by mass of peat, a product of the input of plant tissues and litter and the output of decomposition under aerobic and anaerobic conditions. We examined patterns of these elements, as the O:C and H:C atomic ratios, in over 1, 300 peat samples collected from over 400 profiles in Ontario, Canada, representing bogs, fens, and swamps. The overall O:C ratio decreased from the surface (0.6 to 0.7) to ~0.5 at a depth of 50 cm and showed little further change to a depth of 5 m. In contrast, the H:C ratio decreased only slightly (1.30 to 1.25) over the top 1 m and showed no further significant decline with depth. The C oxidative state (Cox ) and oxidation ratio showed strong decreases and increases, respectively, with depth with most changes occurring in the top 0.5 m. The O:C ratio, and Cox and oxidation ratio values were significantly correlated with the von Post humification index, with most changes occurring in index values 1 through 4, the latter representing a slight degree of decomposition. Collation of the Ontario peats with other data sets revealed the very large range in O:C and H:C values, with a general decrease from temperate to tropical and subtropical peatlands. Estimation of the O:C and H:C ratios of input (litter) and output (mineralization to CO2, methanogenesis to CH4 and CO2, and loss as dissolved organic C) allowed an estimation of the degree of decomposition or C loss. Plain Language Summary: Carbon, hydrogen, and oxygen form about 90% of the mass of peat, derived from the decomposition of dead plant and animal material. Using a large database from bog, fen, and swamp peatlands in Ontario and in Europe, North America, and Indonesia, we show that the ratios, or stoichiometry, between these three elements is a function of their input in litter and decomposition pathways and intensity. We suggest that the ratios, particularly the atomic oxygen:carbon ratio, can be used to predict the proportion of carbon that has been lost through decomposition and peat formation. Key Points: C, H, and O form 90% of peat mass; O:C but not H:C ratio decreases with depth in Ontario peatlands The O:C and H:C ratios are a function of their input in litter and pathways and degree of decomposition in peat formation The O:C ratio and stoichiometry of decomposition may be used to predict the proportion of C that has been lost since peat formation